Quantitation of proteinuria in nephrotic syndrome by spot urine protein creatinine ratio estimation in children - Biswas, Arnab; Kumar, R; Chaterjee, A; Ghosh, JK; Basu, K (Mymensingh Medical Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Mymensingh Med J. 2009 Jan;18(1):67-71. The abstract of this article is available on the PubMed website